Earth story : the shaping of our world - Lamb, Simon; Sington, David (Princeton, N.J. : Princeton University Press, 1998)
Studies the constant environmental changes that are occurring on Earth and discusses what causes these changes, how they affect the Earth, how all the Earth's systems are interlinked, and other related topics.
"Published to accompany the television series Earth story, which was first broadcast on BBC 2 in 1998"--T.p. verso.
Includes bibliographical references (p. 234) and index.
Library Journal.
Publisher's Weekly.
University Press Titles (A.A.S.L./P.L.A.).
Adult
Keywords: Historical geology; Geology; Stratigraphic geology